2014
DOI: 10.1371/journal.pone.0088418
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Case-Control Analysis of the Outpatient Expenditures for Western Medicine and Dental Treatment Modalities in CKD Patients in Taiwan

Abstract: BackgroundTo determine if expenditures for dentistry (DENT) correlate with severity of chronic kidney disease (CKD).MethodsA total of 10,457 subjects were enrolled from January 2008 to December 2010, divided into three groups: healthy control (HC) group (n = 1,438), high risk (HR) group (n = 3,392), and CKD group (n = 5,627). Five stages were further categorized for the CKD group. OPD utilization and expenditures for western medicine (WM), DENT, and TCM (traditional Chinese medicine) were analyzed retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This nationwide hospital-based study recruited individuals from National Health Insurance Research Database (NHIRD), released by the National Health Research Institutes (NHRI). Taiwan launched its National Health Insurance Program (NHIP) on 1st March 1995, and by 2009, a coverage rate of the program had reached 99% of the population 8, 15. The NHIRD contains complete medical information of all insured individuals, including diagnoses, healthy services and claims records for reimbursement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This nationwide hospital-based study recruited individuals from National Health Insurance Research Database (NHIRD), released by the National Health Research Institutes (NHRI). Taiwan launched its National Health Insurance Program (NHIP) on 1st March 1995, and by 2009, a coverage rate of the program had reached 99% of the population 8, 15. The NHIRD contains complete medical information of all insured individuals, including diagnoses, healthy services and claims records for reimbursement.…”
Section: Methodsmentioning
confidence: 99%
“…Although the exact causal associations between diseases is complicated, 5 it is widely accepted that CKD can affect the oral health status; likewise, poor oral health has influence on the progression of CKD 4, 5, 6, 7. Accordingly, these findings would justify an greater attention and awareness to dental care in CKD patients 4, 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the risk of fracture is significantly higher in chronic kidney disease (CKD) patients than in the general population [21]. The expenditures of oral problems also increased steadily along with the severity of CKD stages [22]. Homeostasis of calcium and phosphate maintain the development of bones.…”
Section: Kidney Controls the Bonesmentioning
confidence: 99%
“…In CKD patients salivary cytokines and secretion rates are signi icantly decreased (Thorman et al, 2010). Structural equation models exploring the bidirectional relationship of CKD and periodontitis suggested that CKD may have direct effect on moderate periodontitis, and that individuals with moderate periodontitis were more likely to have CKD (Ioannidou et al, 2011b;Pradeep et al, 2012;Dağ et al, 2010;Huang et al, 2014).…”
mentioning
confidence: 99%